Insights into Conifer Giga-Genomes. Issue 4 (27th October 2014) - De La Torre, Amanda R.; Birol, Inanc; Bousquet, Jean; Ingvarsson, Pär K.; Jansson, Stefan; Jones, Steven J.M.; Keeling, Christopher I.; MacKay, John; Nilsson, Ove; Ritland, Kermit; Street, Nathaniel; Yanchuk, Alvin; et al.
Abstract : The sequenced genomes of three conifer species provide the first assemblies of gymnosperm genomes and perspectives on the largest plant genomes sequenced to date . Abstract: Insights from sequenced genomes of major land plant lineages have advanced research in almost every aspect of plant biology. Until recently, however, assembled genome sequences of gymnosperms have been missing from this picture. Conifers of the pine family (Pinaceae) are a group of gymnosperms that dominate large parts of the world's forests. Despite their ecological and economic importance, conifers seemed long out of reach for complete genome sequencing, due in part to their enormous genome size (20–30 Gb) and the highly repetitive nature of their genomes. Technological advances in genome sequencing and assembly enabled the recent publication of three conifer genomes: white spruce ( Picea glauca ), Norway spruce ( Picea abies ), and loblolly pine ( Pinus taeda ). These genome sequences revealed distinctive features compared with other plant genomes and may represent a window into the past of seed plant genomes. This Update highlights recent advances, remaining challenges, and opportunities in light of the publication of the first conifer and gymnosperm genomes.